WACANA REFORMIS DALAM TAFSIR MADURA: Analisis Penafsiran Mudhar Tamim dalam Tafsir Alqur’anul Karim Nurul Huda - Kamil, Ahmad Zaidanil (STAI AL-ANWAR SARANG, 2022)
Abstract This paper reviews reformist narratives in the Madurese language interpretation of the Qur'an entitled Tafsir Alqur'anul Karim Nurul Huda. Written in 1969 by Mudhar Tamim (1916-2000), a religious leader, intellectual, politician and freedom fighter from Pamekasan, Madura. This research is a qualitative research model of literature (library research). Through the perspective of critical insight analysis, this paper seeks to show how ideological reformers have influenced Madurese interpretations. The results of this study indicate that Mudhar Tamim used the interpretation of the Qur'an as a means of voicing reformist ideas as a reaction against traditionalist Madurese Muslims. This reformist narrative can be seen from the criticism of taklid culture, rituals of ecological adaptation, and the practice of Sufism. This third aspect is packed with critical narratives. As one of the interpretations of Madurese Muslim works, Tafsir Al-Qur'anul Karim Nurul Huda is important to study. Not only enriches literature, discourse and discourse around the tradition of exploring the Qur'an in Madura, but also captures how the struggle for discourse on religious ideology in Madura.